Effects of chicory on pancreas status of rats in experimental dislipidemia - Kocsis, Ibolya (Acta Biologica Szegediensis, 2003)
The well known medicinal plant, Cichorium intybus L. (Asteraceae) contains dietary oligofructose compounds which have beneficial effect on carbohydrate and lipid metabolism, other compounds e.g. polyphenol type derivatives could be responsible for the antioxidant properties reported in several studies before. Male Fischer rats were kept on normal and lipid rich diet supplemented with chicory extract in this study. Our aim was to investigate the influence of this supplementation on pancreas status of rats, especially in dislipidemia. Polyphenols, flavonoids and caffeic acid derivatives were measured in chicory extract by spectrophotometric and chromatographic methods. Antioxidant property of the plant extract was determined in vitro and the biological activity of antioxidant compounds of chicory was investigated in vivo by a luminometric technique.The effects of bioactive molecules of chicory extract influenced the lipid metabolism and the redox balance of pancreatic tissue of rats in experimental dislipidemia.